THE SPREAD OF THE HANAFI SECT IN MOVAROUNAHR AND THE SERVICES RENDERED BY THE SCHOLARS TO THE SECT - Rozmetov Muhammad Mustafa (Web of Journals Publishing, 2024)
For independent researchers who are doing scientific work in the study of jurisprudence and who intend to do a comparative analysis of the books written in the Hanafi madhhab, it is necessary to learn first of all who are the jurists of the madhhab and their services. Because the Hanafi madhhab was developed by the famous jurists of the madhhab. This article talks about the spread of the Hanafi Madhhab Movarounnahr and the jurists who distinguished themselves by some of their merits.
Keywords: Movarounnahr, fiqh, faqih, madhhab, hanafi, waqeot, fatawa, fuqaha.